Poster 178: Blood Flow Restriction Therapy Before and After Arthroscopic Rotator Cuff Repair. Issue 7 (30th July 2022) - Castle, Joshua; Jildeh, Toufic; McGee, Anna; Abbas, Muhammad; Buckley, Patrick; Okoroha, Kelechi; Kolowich, Patricia; Moutzouros, Vasilios; Tramer, Joseph
Objectives: To evaluate the effect of blood flow restriction (BFR) therapy conducted before and after rotator cuff repair (RCR) on rotator cuff strength and patient reported outcomes. Methods: A total of 30 patients (22 male, 8 female; age 58.2 ± 9.0 years) presenting for surgical treatment of a rotator cuff tear were randomized into two groups, BFR (N=15) and Control (N=15). Rotator cuff strength was measured utilizing a handheld dynamometer in order to calculate peak force, average force and time to peak force. Strength measurements included supraspinatus, infraspinatus and subscapularis testing in multiple positions. Prior to surgery, patients completed a rotator cuff strengthening program, with and without the use of BFR. All patients underwent arthroscopic RCR and a standardized period of post-operative immobilization. Following surgery, patients underwent physical therapy utilizing standard post-RCR therapy protocols, with exercises performed with and without the use of BFR in each respective group. The BFR group was instructed to perform these exercises with a pneumatic cuff set to 80% of limb occlusion pressure placed over the proximal arm, under the direction of a physical therapist. Patient Reported Outcome Measurement System Upper Extremity (PROMIS-UE), American Shoulder and Elbow Surgeons (ASES) score and shoulder range of motion were collected on the day of surgery as well as 2 weeks, 6 weeks and 3 months after surgery. Rotator cuff strength measurements were completed the day of surgery and repeated three months following RCR. Results: No significant differences were noted between the BFR and control groups in peak rotator cuff muscle force generation, time to peak force or average force at any timepoints (P>0.05). At six weeks post-surgery, the BFR group had significantly higher PROMIS-UE scores (30.3 ± 4.7 versus 26.3 ± 6.3, p=0.03, Figure 1) and active range of motion in abduction (82.4º ± 24.7 versus 65.1º ± 18.8, p=0.03) compared to the control group. These differences were not apparent at 3 month follow up. Conclusions: Blood flow restriction therapy following RCR results in improved patient reported outcomes scores and range of motion at six week follow up. At three months post-surgery, there was no noted improvement in rotator cuff strength when utilizing BFR compared to standard physical therapy.